PENGEMBANGAN MEDIA PERMAINAN SIMULASI ULAR TANGGA UNTUK MENINGKATKAN TANGGUNG JAWAB BELAJAR SISWA SMP - Putri, Sekar Ariyanti; Ramli, M. (Jurnal Kajian Bimbingan dan Konseling, 2016)
The purpose of this research development is to generating snakes and ladders simulation game media for increasing academic responsibility of junior high school students that meet eligibility criteria. The step development is (1) initial data collection, (2) planning, (3) developing product, (4) validity product, (5) test run product, (6) revision final product. Research result showed that snakes and ladders simulation game for increasing academic responsibility of junior high school students are qualified and worthy of display media used to provide guidance about academic responsibility.